IMPLEMENTASI EKSEKUSI PENINJAUAN KEMBALI TERHADAP NAMA BAIK NOTARIS YANG DIPUTUS TIDAK BERSALAH (STUDI PUTUSAN PENINJAUAN KEMBALI NOMOR : 14/PK/PID/2012) - ANDIANY PUTRI MERDEKAWATY (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Notaris Dr. Henry Sinaga, SH, MKn3. Dr. M. Hamdan, SH, MHumA suspect’s good name will be a problem when he is free by a court’s verdict. When a defendant is on trial and is found not guilty and set free from any prosecution, he has the right to get rehabilitation from the court. The research problems are how about the implementation of the execution in judicial review on a Notary’s good name when he is found not guilty and how about the position of a Notarial deed in the post-verdic of judicial review. The research used juridicial normative method with descriptive analytic approach. The data were gathered by conducting library research and field research methods. A defendant who is set free from any prosecution, does not sue for compensation, and is not imprisoned, can make a request to the Panel of Judges to rehabilitate his good name through newspapers or other printed media and make civil complaint and file a claim. It is recommended that to get compensation and rehabilitation for good name on a defendant who is found not guilty, not file a complaint to the court.Keywords : Notary, Judicial Review, Rehabilitation for Good Name